2013
DOI: 10.1111/ap.12015
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Attentional Strategies on Physiological and Psychological States During Running

Abstract: The attentional focus of an athlete or recreational exerciser may influence performance outcomes during running. The present study used an experimental approach to manipulate the associative attentional focus of regular exercisers (n = 21) as they ran on a treadmill at 75% of Vmax. Participants focused their attention on their breathing, running movements, the distance travelled, or under no specific instructions (control). A focus on distance travelled produced the lowest respiration frequency, and a focus on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 47 publications
(87 reference statements)
3
15
1
Order By: Relevance
“…Furthermore, intensity level was determined differently in the two studies, which leads to difficulties in directly comparing them. Results of a recent study by Neumann and Piercy (2013) are, as well, in contrast to the present results. They found lowest VO 2 in the internal running movement condition, compared with a breathing focus, an external focus, and a control condition.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, intensity level was determined differently in the two studies, which leads to difficulties in directly comparing them. Results of a recent study by Neumann and Piercy (2013) are, as well, in contrast to the present results. They found lowest VO 2 in the internal running movement condition, compared with a breathing focus, an external focus, and a control condition.…”
Section: Discussioncontrasting
confidence: 99%
“…Gröpel (2016) showed that giving instructions that induced self-focused attention resulted in worse free throw accuracy in state-oriented basketball players whereas there was no effect of the instructions on action-oriented players. These findings are in line with research showing that it is better to focus externally, on specific cues associated with movement, to achieve better accuracy in aiming sports (Wulf & Lewthwaite, 2016) and movement economy (Neumann & Heng, 2011;Neumann & Piercy, 2013). Another method, which is broader in approach than to adopt a specific type of attentional focus, is require the athlete to achieve a given standard of performance through setting goals (Gould, 2006;Locke & Latham, 1990;Weinberg, 2013).…”
Section: Introductionsupporting
confidence: 85%
“…The findings are promising but are in need of replication and extension. Past research with non-VR tasks has also found that an external associative focus enhances sport and exercise outcomes (e.g., Neumann and Heng 2011;Neumann and Piercy, 2013). An external associative focus involves focussing on the effects of movements on the environment and the achievement of task goals (Neumann and Brown, 2013;Stevinson and Biddle, 1999).…”
Section: Future Research Directions and Recommendationsmentioning
confidence: 99%